2014
DOI: 10.1590/s0104-64972014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Living with a crab: effect of Austinotheres angelicus (Brachyura, Pinnotheridae) infestation on the condition of Saccostrea palmula (Ostreoida, Ostreidae)

Abstract: -Some members of the Pinnotheridae family exhibit close symbiotic relationships with bivalves, which may cause severe damage to the mollusk. The condition index (CI) is a tool that serves to evaluate the effect of biotic and abiotic factors on the morphology and physiology of mollusks, including those caused by symbiotic organisms. In the present study, we evaluated the effects of the infestation of the pinnotherid crab Austinotheres angelicus on the oyster Saccostrea palmula through monthly sampling (April to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
13
2
Order By: Relevance
“…Concerning crab pairs, there was a remarkable increase between October 2017 (3.3% of hosts infested) and February 2018 (26.7% infested). A positive relationship between crab prevalence and the proportion of multiple infested hosts has been found in other pinnotherid crabs (Asama & Yamaoka, 2009; Mena et al ., 2014; Pérez-Miguel et al ., 2019). Thus, it is not possible to reject the view that the increased multiple infestations may be partially associated with the increase in the proportion of hosts infested by P. bicristatus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning crab pairs, there was a remarkable increase between October 2017 (3.3% of hosts infested) and February 2018 (26.7% infested). A positive relationship between crab prevalence and the proportion of multiple infested hosts has been found in other pinnotherid crabs (Asama & Yamaoka, 2009; Mena et al ., 2014; Pérez-Miguel et al ., 2019). Thus, it is not possible to reject the view that the increased multiple infestations may be partially associated with the increase in the proportion of hosts infested by P. bicristatus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other marine invertebrates such as bivalves (Salas-Moya et al 2014) and ascidians (Levitt-Barmats & Shenkar 2018) that host endosymbiotic crustaceans, the snail M. patula is a large and morphologically complex host which is capable of housing up to two porcelain crabs in the mantle cavity. Our observations coincide with those of Telford and Daxboeck (1978) who found up to two specimens of the crab Porcellana gayana on the inner surface of the operculum of the snail Strombus gigas.…”
Section: Discussionmentioning
confidence: 99%
“…Baeza et al (2013) described the sexual and mating system of the shrimp Paranchistus pycnodontae Bruce, 1978, inhabiting the penguin's wing oyster Pteria penguin Röding, 1798, in Papua New Guinea. On the Pacific coast of Costa Rica, Mena et al (2014) Although most porcelain crab species are free-living (Rodríguez et al 2005), many of them have been found in endo or ectosymbiotic relationships (living inside or outside of the host, respectively) living as parasites, commensalistic or mutualistic relationships with a variety of organisms such as anemones (Baeza & Stotz 2003, López-Victoria et al 2004 The following measurements of the Melongena patula shell were obtained with a caliper (± 0.01 mm); the total height (TH) from the apex to the siphon channel; the total width (TW) from the most distal point of the opening parallel to the apex to the most distal part of the outer lip; the height of the opening (HO) from the exhalation channel to the siphonal channel; the width of the opening (WO) or the most distal distance between the inner and outer lips; and the operculum width (OW) or the distance between the points perpendicular to the maximum length of the operculum (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Mortality could be selectively removing the less-fit individuals of the population in the field, and as a result larval duration of survivors could be slightly shorter than that estimated under culture conditions (Dickey-Collas et al 2000). Some pinnotherids parasitize commercially exploited bivalves (Silas & Alagarswami 1967;Sun et al 2006;Mena et al 2014), with a significant loss of production detected in some shellfish farms (Trottier et al 2012). As males and females of Afropinnotheres monodi display an asymmetrical use of different bivalve hosts, the strongest infestation by this pea crab was expected to be found in shellfish exploitations located where their various hosts coexist; that is, in sheltered waters such as bays, inlets, rías and harbours (Drake et al 2014).…”
Section: Dispersal Capability Of Afropinnotheres Monodimentioning
confidence: 99%